Flerbostadshuset i fokus: ekonomi och hållbarhet i energiomställningen - Fondelius,Fabian; Irahoza,Joël (2025)
Property owners face increasing pressure from new EU regulations on energy and sustainability, coupled with rising utility costs. This study investigates the profitability of energy efficiency measures for property owners aiming to navigate these new demands while achieving economic sustainability. The EU's climate strategy, including the Green Deal and directives like CSRD, EPBD, and the EU Taxonomy, mandates enhanced sustainability in the building sector. This necessitates reducing climate impact and directing investments towards greener alternatives. Energy efficiency has become a strategic imperative for property owners, driven by both cost savings and regulatory compliance. A particular challenge is the high conversion factor for electricity in energy performance certificates, which can negatively impact the energy class of electrically powered properties. The future development of this factor is crucial for electricity-based solutions like ground-source heat pumps. We used detailed computer simulations with IDA ICE software on two real multidwelling buildings in Örkelljunga municipality. By testing various energy efficiency measures, we calculated energy savings and their long-term financial impact. Results indicate that measures like external wall insulation and upgrading existing ventilation systems are economically advantageous and profitable. Ground-source heat pump installations also show long-term profitability despite higher initial costs. Conversely, measures such as window replacement and converting from simpler (Fsystem) to more advanced ventilation systems (FTX) were economically challenging due to high investment costs relative to achieved energy savings. This highlights the importance of object-specific analyses. A key finding is that an improved energy performance class does not always correlate with improved profitability, partly due to how energy classes are calculated. Therefore, property owners should consider economic metrics like net present value and payback period, not just energy performance classes, to make informed decisions for true environmental and economic sustainability.
Keywords: Energieffektivisering; Flerbostadshus; Hållbarhet; Lönsamhetsanalys; Energiomställning; EU-direktiv; EPBD; CSRD; EU-taxonomin; IDA ICE; Simulering; Återbetalningstid; NNV; Renovering; Energiklassificering.